(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Educational institutes have always been called the second home of students. This is where the knowledge is acquired, learned, and practiced. Aside from educational learning, students also get discipline, manners, and skills. Every moment spent in school is considered a lesson in itself. Entering school also means leaving the first home in the meantime. However, the needs of the students are being catered to inside the school. Some schools also have food courts where independent food stalls are placed. Considering the school as the second home, students expect a service that equates to what they experience at their homes, including the proper serving of food and cleanliness assurance. The model stated that consumers’ quality perceptions are influenced by a series of four distinct gaps. These gaps are on the provider’s side, where the customer’s perception of service quality comes from. One hundred college students were randomly selected from the school and were chosen to answer the Four-point Likert Scale questionnaire, which will be the instrument to gather data. The data-gathering procedure came to the conclusion that there is a significant relationship between the service quality of selected food stalls and customer satisfaction, given that three domains significantly influence customer satisfaction. Those three domains are tangibility, reliability, and responsiveness. Also, the respondents perceive all five domains of service quality (tangibility, assurance, reliability, responsiveness, and empathy) as very satisfactory. Moreover, the p-value of 0.023 is less than the alpha 0.05. Therefore, the Alternative hypothesis is accepted.